Targeting the LKB1 Tumor Suppressor - Zhao, Rui-Xun; Xu, Zhi-Xiang (Current Drug Targets, 2014)
LKB1 (also known as serine-threonine kinase 11, STK11) is a tumor suppressor, which is mutated or deleted in Peutz-Jeghers syndrome (PJS) and in a variety of cancers. Physiologically, LKB1 possesses multiple cellular functions in the regulation of cell bioenergetics metabolism, cell cycle arrest, embryo development, cell polarity, and apoptosis. New studies demonstrated that LKB1 may also play a role in the maintenance of function and dynamics of hematopoietic stem cells. Over the past years, personalized therapy targeting specific genetic aberrations has attracted intense interests. Within this review, several agents with potential activity against aberrant LKB1 signaling have been discussed. Potential strategies and challenges in targeting LKB1 inactivation are also considered.
Keywords: targeting therapeutics